Sistem penunjang keputusan pemilihan karyawan garmen terbaik Menggunakan metode Weighted Product - Cahya Annisyah Waruwu; Ucta Pradema Sanjaya (Jurnal Algoritma, 2026)
The garment industry sector is highly dependent on human resources to play a role in maintaining quality at every stage of the production process and final products. Employee assessment methods in this sector tend to rely on subjective evaluations, which can lead to potential unfairness in decision-making. This study discusses the development of a decision support system that can be used by management to identify employees in a more objective manner. The method applied in this research is the Weighted Product method, which evaluates a number of alternatives by multiplying rating values derived from several criteria, namely punctuality, discipline, work quality, responsibility level, and teamwork. Employee data were obtained through interviews and observations in the production department. The calculation results indicate that the Weighted Product method is able to generate more consistent and objective employee rankings. The system is implemented as a web-based application so that it can be accessed by management. With the implementation of this system, the employee evaluation process becomes more efficient and transparent and can be used as a basis for awarding incentives and job promotions.